Chitosan-Tripolyphosphate Nanoparticles Prepared by Ionic Gelation Improve the Antioxidant Activities of Astaxanthin in the In Vitro and In Vivo Model - Eun Suh Kim; Youjin Baek; Hyun-Jae Yoo; Ji-Soo Lee; Hyeon Gyu Lee (MDPI AG, 2022)
The present study aimed to investigate the effects of chitosan (CS)-tripolyphosphate (TPP) nanoparticles (NPs) on the stability, antioxidant activity, and bioavailability of astaxanthin (ASX). ASX-loaded CS-TPP NPs (ACT-NPs) prepared by ionic gelation between CS (0.571 mg/mL) and TPP (0.571 mg/mL) showed 505.2 ± 184.8 nm, 20.4 ± 1.2 mV, 0.348 ± 0.044, and 63.9 ± 3.0% of particle size, zeta potential, polydispersity index and encapsulation efficiency, respectively. An in vitro release study confirmed that the release of ASX in simulated gastric (pH 1.2) and intestinal (pH 6.8) fluid was prolonged within ACT-NPs. The in vitro antioxidant activities of ACT-NPs were significantly improved compared with free ASX (FA) (p < 0.05). Furthermore, the cellular and in vivo antioxidant analysis verified that ACT-NPs could enhance the cytoprotective effects on the BHK-21 cell line and demonstrate sustained release properties, leading to prolonged residence time in the rat plasma. The results suggest that the stability, antioxidant properties, and bioavailability of ASX can be effectively enhanced through encapsulation within CS-TPP NPs.